The The Python Workshop : Learn to code in Python and kickstart your career in software development or data science /: Learn to code in Python and kickstart your career in software development or data science. (2019) - Bird, Andrew; Dr, Han, Lau Cher; Jiménez, Mario Corchero; Lee, Graham; Wade, Corey
No abstract available